DAMPAK KEBIJAKAN ZONASI TERHADAP KUALITAS PEMBELAJARAN PAI DI DAERAH PERBATASAN - Nisbaul Nabawi (Yayasan An-Nur Meunara Baro, 2025)
This study examines the impact of school zoning policy on the quality of Islamic Religious Education (PAI) instruction in ten border schools located along the Indonesia–Malaysia and Indonesia–Timor Leste frontiers. Using a mixed-methods approach that combines surveys of 120 PAI teachers and in-depth case studies in five schools, the study finds that zoning policy has exacerbated disparities in PAI instruction quality. Three main mechanisms are identified: (1) unequal redistribution of PAI teachers, leaving border schools without qualified instructors; (2) the lack of significant incentives to attract and retain competent teachers in remote areas; and (3) insufficient religious instructional resources such as learning media and worship facilities. The study also notes the absence of religious education considerations in the current zoning policy framework, which has led to the marginalization of PAI’s role in border school curricula. This research recommends the implementation of geographically targeted affirmative policies to ensure the equitable distribution of qualified PAI teachers, the provision of adequate religious learning infrastructure, and the strengthening of madrasah diniyah networks and local religious institutions. The findings are expected to contribute to the development of a more inclusive and context-sensitive educational policy framework.